2022
DOI: 10.17507/tpls.1202.06
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Factors and Intended Efforts in Learning East Asian Languages Among Thai Undergraduate Students

Abstract: The objective of the current study was to investigate undergraduate students’ motivation in learning three East Asian languages (Chinese, Japanese, and Korean), with intended effort used as a measure of motivation, based on Dörnyei’s L2MSS theory (2005) and five other predictors. The study’s participants were 95 undergraduate students, recruited by convenient random sampling on a voluntary basis, eight of whom volunteered to participate in interviews. Descriptive data and Pearson correlations were used to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…In the study conducted by Praneetham et al (2022), the desire to travel to a country where the target language is spoken was identified as a factor influencing students' motivation; however, it should be noted that it was not the primary reason mentioned by the students. Nevertheless, the findings of the current study align with those of Yang and Chanyoo (2022), which revealed a positive association between Cultural/Community Interest and Japanese learners.…”
Section: Culture/community Interest and Instrumentality-promotionsupporting
confidence: 85%
See 2 more Smart Citations
“…In the study conducted by Praneetham et al (2022), the desire to travel to a country where the target language is spoken was identified as a factor influencing students' motivation; however, it should be noted that it was not the primary reason mentioned by the students. Nevertheless, the findings of the current study align with those of Yang and Chanyoo (2022), which revealed a positive association between Cultural/Community Interest and Japanese learners.…”
Section: Culture/community Interest and Instrumentality-promotionsupporting
confidence: 85%
“…The findings revealed that English and Korean students reported the Ought-to L2 Self as their primary source of motivation, while French, Chinese, and Japanese students reported the Past L2 Learning Experience. In addition, Yang and Chanyoo (2022) conducted another mixed-methods study to examine the motivation of Thai undergraduate students in learning three East Asian languages: Chinese, Japanese, and Korean. The researchers measured motivation using intended effort, drawing on Dörnyei's (2009) L2MSS theory and five additional predictors.…”
Section: Lote Motivational Studies In Thai Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is extensive research on the L2 motivation self system (L2MSS) [6][7][8][9][10][11][12] and several studies on international posture [13][14][15], as well as the relationship between the two [16][17][18]. However, there is scarcely any study that examines the relationship between L2MSS, international posture, and L2 proficiency simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…As summarized by Mendoza and Phung (2019), only about 27% of studies were dedicated to LOTEs, either independently or in conjunction with English. As a result of this great language bias, many recent scholars have called for more research on the motivation for LOTEs (Chanyoo, 2022;Yang & Chanyoo, 2022).…”
Section: Introductionmentioning
confidence: 99%